Therapeutic potential of bixin on inflammation: a mini review - Shadisvaaran, Saminathan; Chin, Kok-Yong; Mohd-Said, Shahida; Leong, Xin-Fang (Frontiers in Nutrition, 2023)
Chronic inflammation is the underlying mechanism for many diseases. Thus, inflammatory signaling pathways are valuable targets for new treatment modalities. Natural products have gained interest as a potential source of bioactive compounds which provide health benefits in combating inflammatoryrelated diseases. Recent reports have linked the medicinal values of Bixa orellana L. with its antiinflammatory activities. Therefore, this review aims to examine the therapeutic potential of bixin, a major bioactive constituent found in the seeds of B. orellana, on inflammatory-related diseases based on existing in vitro and in vivo evidence. Additionally, the anti-inflammatory mechanism of bixin via signaling pathways is explored and possible toxic effects are addressed. The findings suggest that bixin may ameliorate inflammation via inhibition of toll-like receptor 4/nuclear factor-kappa B (TLR4/NF-κB), phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) and thioredoxin-interacting protein/NODlike receptor protein 3 (TXNIP/NLRP3) inflammasome mechanisms. More well-planned clinical studies should be performed to verify its effectiveness and safety profile.